Fortalecimiento de potencialidades ambientales mediante la aplicación de educación ambiental no formal para la conservación del barranco Alonso Alvarado Cuadra 15 - López Villarreal, Cintya Vanessa (2015)
The present investigation work of applicative character called: "Strengthen the environmental potential through the application of non-formal environmental education for the conservation ofthe Alonso Alvarado ravine block 15; Moyobamba 2013", establishes an environmental diagnostic initial and end in the topics (water, soil, air, flora, fauna and solid waste) ofthe Alonso Alvarado ravine population; as well as to strengthen the environmental potential as the start the solid waste segregation. This work focused on the implementation of envimnmental educatjon to stiengthen the environmental potential with the purpose to raise the knowiedge neighbors in environmental issues; to get to meet the objectives of this research methodology was used, techniques and materials characteristic of the regular basic education that helped in the process of teaching and learning in the themes developed. The study was conducted with 62 inhabitants; m the results obtained in this investigation was unable to establish: Before the implementation ofthe solid waste program, the learning of concepts of the neighbors who airead y have a substantial level of knowledge on this topic, on a scale of O - 1 O, with a 32.26 %, this is due to that prior to the implementation of the program already had a population dedicated to carry out these activities in the Alonso Alvarado ravine, at the end ofthe implementation ofthe program on a scale of 11 - 13 and 14- 17, there is a 70.97% and 20.97 %, to increase their knowledge respectively; it is note a uniformity in the percentages with respect to the initial evaluation, it being shown that the program a significant influence on the surrounding neighbors ofthe Alonso Alvarado ravine-Moyobamba 2013. Before the implementation of the solid waste program evaluation of solid waste separation, the highest percentage of students on ~ scale of O - 1 O and 11 - 13, was found a 59.68 % and 40.32 %, respectively of learning and at the end of the implementation ofthe program the neighbors toa scale of 11-13 and 14-17, achieved a 64.52% and 27.42 %, to increase their knowledge ofrespectively; proving that the so lid waste program has influenced the learning of the so lid waste management in the neighbors surrounding the Alonso Alvarado ravine, Moyobamba 2013. Before the implementation ofthe solid waste program, the level ofcapacity building in the solid waste management most ofthe neighbors toa scale of0-10% and 11-13 %, achieved a 48.39 % and 51.61 %, respectively of strengths and after the implementation ofthe program on a scale of 11-13 and 14-17, achieved a 79.03 % and 14.52 %, the strengthening, respectively; proving that the solid waste program has influenced the strengthening of capacities at the adjacent neíghbors ofthe Alonso Alvarado ravine, Moyobamba 2013. Results demonstrate that it is in the hypothesis test in this investigation of character applicative in which the knowledge of the inhabitants; increased in the differeni themes developed within and outside the Alonso Alvarado ravine. The 4 implementation of environmental education influences in the strengtheníng of nonformal environmenta] potentials for the conservation of the Alonso Al varado ravine block 15; Moyobamba 2013. Key words: solid waste segregation, knowledge.